The Tension Between Flexible Goals and Managerial Control in Exploratory Projects. Issue 5 (October 2019) - Loch, Christoph; Sommer, Svenja
Over the last 20 years, research on the management of exploratory projects has shown the need for flexible execution methods. However, while the managers involved in such projects recognize the need for flexibility in the means, supervising managers are reluctant to provide flexibility in evolving project goals . Indeed, supervising managers tighten control rather than loosen it when projects become more uncertain. We show empirical evidence of how this resistance emerges in the gray area between "being flexible on the means" and "losing control." We also offer proposals on how to make exploration projects more acceptable to top management.